Innovative methods for cleaning drilling mud - Voita, M. O.; Pashchenko, O. A. (НТУ ДП, 2024)
Drilling mud, also known as drilling fluid, is a crucial component in oil and gas drilling operations. It serves multiple essential functions, including lubricating the drill bit, carrying rock cuttings to the surface, controlling pressure in the wellbore, and preventing formation damage. The composition of drilling mud varies but typically includes water or oil-based fluids, additives, and solids like clay or barite.
Keywords: Innovative methods; cleaning drilling mud